MEWUJUDKAN MASYARAKAT DAMAI DAN INKLUSIF: ANALISIS IMPLEMENTASI TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS 16) DALAM KONTEKS HUKUM ADAT DI INDONESIA - Roberth Kurniawan Ruslak Hammar; Agustinus Luturmas (PATRIOT, 2025)
This article examines the relevance of Sustainable Development Goal (SDG) 16, which emphasizes peace, justice, and strong institutions, in relation to the practice of customary law (hukum adat) in Indonesia. Employing a normative–juridical approach and the framework of legal pluralism, the study analyzes the role of customary law as a social instrument that safeguards harmony, provides access to justice, and strengthens local institutions. Case studies from indigenous communities in Papua, Maluku, and Kalimantan demonstrate that customary dispute resolution mechanisms—such as Pela Gandong, Bakar Batu, and Dayak ulayat rights—are effective in creating social reconciliation and maintaining community stability. The findings confirm that customary law is not merely a cultural heritage but also a crucial pillar of sustainable development. Consequently, formal state recognition of customary institutions is essential to support the achievement of the 2030 SDGs, particularly in realizing a peaceful, inclusive, and just society.